Analisis Problematika Pembelajaran Pendidikan Agama Islam - Abu Hasan Al Asy’ari (Khazanah : Journal of Islamic Studies, 2023)
Among the effective ways that can be done in maintaining the existence of Islam is to study and explore it. Islamic Religious Education is a subject whose purpose is to understand Islam well and do charity correctly. This paper wants to analyze the problems of learning Islamic Religious Education. This paper uses a qualitative method of literature study by tracing various authoritative sources. The results of this study show that the problems faced in the learning process of Islamic Religious Education come from students, namely: 1) Lack of understanding of the material provided by the teacher, 2) Low student learning motivation, 3) there are still many students who are not able to read the Qur'an. Problems that come from educators, namely: 1) The lack of teacher competence in mastering classes, and 2) the lack of teacher competence in mastering learning materials. Meanwhile, the efforts made to overcome the learning problems of Islamic Religious Education are: 1) striving to create a conducive learning environment; 2) strive to increase student motivation, namely by giving advice so that students are more enthusiastic about learning, 3) rewarding students in the form of grades and praise for student success in learning, and 3) monitoring or assessing educators as evaluation material.